2007
DOI: 10.1111/j.1399-3062.2007.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic agents of diarrhea in solid organ recipients

Abstract: : After transplantation, diarrhea may be caused by infectious agents, drug‐specific effects, metabolic conditions, or mechanical complications of surgery. Determining the cause helps to determine whether to initiate antimicrobial therapy and the duration of treatment. In this study we aimed to determine the causes of diarrhea in kidney or liver recipients. Fifty‐two diarrhea episodes among 43 solid organ recipients were evaluated. The cause of diarrhea was detected in 43 patients (82.6%). Infectious etiologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
83
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 22 publications
8
83
2
2
Order By: Relevance
“…In practice, negative microbiological diagnosis leads nephrologists to perform invasive complementary tests like colonoscopy and often to modify immunosuppressive treatment considered to be the cause of diarrhea, with a risk of acute or chronic transplant rejection (9)(10)(11). Yet in various studies, it has been reported that, in 38 to 64% of cases, diarrhea was of infectious origin (1,(12)(13)(14). The implicated microorganisms corresponded mainly to enteric bacteria (Campylobacter spp., enterovirulent Escherichia coli, Salmonella spp., Clostridium difficile), parasites (Giardia intestinalis), and viruses (Norovirus and Rotavirus) that are already responsible for gastroenteritis in the general population (1,2,6,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, negative microbiological diagnosis leads nephrologists to perform invasive complementary tests like colonoscopy and often to modify immunosuppressive treatment considered to be the cause of diarrhea, with a risk of acute or chronic transplant rejection (9)(10)(11). Yet in various studies, it has been reported that, in 38 to 64% of cases, diarrhea was of infectious origin (1,(12)(13)(14). The implicated microorganisms corresponded mainly to enteric bacteria (Campylobacter spp., enterovirulent Escherichia coli, Salmonella spp., Clostridium difficile), parasites (Giardia intestinalis), and viruses (Norovirus and Rotavirus) that are already responsible for gastroenteritis in the general population (1,2,6,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Yet in various studies, it has been reported that, in 38 to 64% of cases, diarrhea was of infectious origin (1,(12)(13)(14). The implicated microorganisms corresponded mainly to enteric bacteria (Campylobacter spp., enterovirulent Escherichia coli, Salmonella spp., Clostridium difficile), parasites (Giardia intestinalis), and viruses (Norovirus and Rotavirus) that are already responsible for gastroenteritis in the general population (1,2,6,(12)(13)(14)(15)(16). However, some pathogens, like human cytomegalovirus (CMV), microsporidia, and cryptosporidia, were specifically found in immunocompromised patients (1,12,13,(17)(18)(19)(20)34).…”
mentioning
confidence: 99%
“…The difference in the prevalence from the previous studies could be due to the differences in the methods of identification (ie, stool examination in previous studies versus only duodenal biopsy in our study). 6,11 Several nonspecific histologic changes have been identified with giardiasis infestation in the normal population, including increases in intraepithelial lymphocytes, changes in villous 149 architecture, presence of lymphoid follicles, and eosinophilic infiltration in the lamina propria. Villous flattening was identified in 33 patients (41.2%) in a study of 80 patients with giardiasis, 12 whereas atrophic villous architecture was observed in 61.2% of patients in another study.…”
Section: Discussionmentioning
confidence: 99%
“…8 After solid-organ transplant, patients are in general more susceptible to opportunistic pathogens than immunocompetent individuals are. 9 Another cause of diarrhea is cytomegalovirus infection with gastrointestinal involvement. In cytomegalovirus enterocolitis, with or without fever, possible complications include gastrointestinal bleeding, perforation, and toxic megacolon.…”
Section: Discussionmentioning
confidence: 99%